Filters in the coping process of people with schizophrenia: A constructivist grounded theory study - Jacques, Marie‐Claude; St‐Cyr Tribble, Denise; Bonin, Jean‐Pierre (Journal of psychiatric and mental health nursing, 2019)
Accessible summary What is known on the subject? In the nursing perspective of Roy’s adaptation model, to be adapted means to have positive interactions with one’s environment. The ability to use effective coping strategies is an essential ingredient of mental health recovery. However, coping difficulties are often a problem for people with a diagnosis of schizophrenia spectrum disorder, especially those who have inadequate social support. What the paper adds to existing knowledge? “Filters in the coping process” is a grounded theory of coping in people with a diagnosis of schizophrenia spectrum disorder. A filter effect impairs their ability and limits their opportunities to use effective coping strategies. These filters are as follows: to have been helped, to understand in one’s own way, to act despite limited freedom and to modulate the process of self‐disclosure. “Surface coping” is the product of the effect of these filters on coping attempts and possibilities. It does not reflect the person’s real potential. What are the implications for practice? By offering an alternative, holistic nursing perspective, the filter model provides the nurse with factors to consider when assessing clients with a diagnosis of schizophrenia spectrum disorder, so as to plan interventions towards improving their coping capacity. By allowing for the presence of surface coping, the nurse will have less tendency to form negative judgments about clients with a diagnosis of schizophrenia spectrum disorder. Introduction Numerous studies confirm the coping difficulties of people diagnosed with schizophrenia spectrum disorder, especially those with limited social support. Further, the coping process is itself poorly understood. Aim Starting from a conceptualization of the adaptation of Roy's model, the aim of this study was to describe the coping process of people with schizophrenia spectrum disorder in the context of an inadequate social support. Method A constructivist grounded theorization was performed with a sample of 30 persons with schizophrenia spectrum disorder. Results The results are a model named: “Filters in the coping process of people with a diagnosis of schizophrenia spectrum disorder who have inadequate social support.” The type of coping strategies used evolves over time and in accordance with the filters. The consequence of the process is “surface coping.” Discussion The coping potential of people with schizophrenia spectrum disorder is affected by environmental factors as well as factors inherent to the disorder itself. The filter model provides a holistic perspective, as opposed to merely focusing on behaviours. Implication for practice The findings of this study could improve nursing interventions through a better understanding of impediments to coping: what they are, how they arise and the nature of their effects.